Police Discretion in Criminal Cases of Abuse by Minors with the Application of Diversion Restorative Justice - Bahari, Virza Imeldha; Enggarani, Nuria Siwi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The objective of this investigation is to analyze the utilization of prudence in the manifestation of restorative justice in solving cases of persecution and to analyze from the perspective of legal sociology the practice of implementing restorative justice in handling cases of abuse. This thesis uses a legal sociology approach with data collection techniques by observation, interviews, and documentation. Factors that led to the crime of persecution: ego factors, economic factors and environmental factors. In cases of abuse, if there are 2 pieces of evidence, namely the statements of 2 witnesses and a post-mortem examination, then the most likely thing is to reduce the evidence, namely witness testimony, so that the witness who has been questioned must withdraw the statement and carry out a special case title to stop the case to determine SP3. The role of Bhabinkamtibmas in restorative justice is as a mediator or facilitator. Bhabinkamtibmas acts as a mediator in solving problems to reduce larger conflicts. Before holding the meeting, Bhabinkamtibmas first accommodated the aspirations of perpetrators and victims who did not want their cases to be processed legally. Bhabinkamtibmas then, together with community leaders, studied the habits of the perpetrators and saw whether this incident could still be repaired. If it can still be repaired, the parties are brought together and followed by deliberations to reach a consensus. Related to the causes of mistreatment of husbands against wives starting from the issue of biological needs, infidelity and economic problems. The positive effects of carrying out mediation for mild abuse by a husband against his wife are Improved husband's behaviour; The creation of household harmony; Re-communication of both sides; Providing a sense of justice to both parties; and settlement of legal issues more quickly and cheaply.